Field theory of multilevel plastic flow in the neck of a deformed solid; Physical Mesomechanics; Vol. 10, iss. 5-6, Sept.-Dec. - Panin V. E. Viktor Evgenyevich (2007, 2007)
The paper demonstrates that the multilevel process of plastic deformation in the neck of a deformed solid can be correctly described with the aid of the field theory of defects. The theory predicts two mechanisms of wave-like plastic flow in the neck. The most common is the multilevel dissipative autowave process based on the self-organization of two localized deformation bands in the neck which are conjugated by the scheme of a cross. This process is accompanied by material fragmentation at the mesolevel, strong work hardening of the material and structure degradation. As a consequence, it is characterized by low plasticity. If self-organization in the neck develops as two macrobands conjugated by the scheme of a dihedral angle, the plastic flow can evolve as a weakly dissipative wave process. It is characterized by very high material plasticity in the neck. The field theory of defects explains well the known experimental data on plastic deformation mechanisms in the neck of a deformed solid